A novel modified SFTA approach for feature extraction - Hasan, Md Junayed; Uddin, Jia; Pinku, Subroto Nag (© 2016 IEEE, 2018)
This conference paper was published in the IEEE Xplore [© 2017 IEEE] and the definite version is available at : http://doi.org/10.1109/CEEICT.2016.7873115 The Journal's website is at: http://ieeexplore.ieee.org/document/7873115/